JOB SATISFACTION LEVEL DETERMINANT OF HYGIENE COLLEGE STAFF (STIKES) HANGTUAH PEKANBARU - Hasrianto, Nofri (Sistem Informasi, 2017)
Globalization era humans have very imperotant role. Factors that can arise motivation and spirit is sense job satisfaction. If there is dissatisfaction from labor hence it will adversely effect to his job causes job satisfaction reflect a person feeling to his job and all he face in his work environment. Problems in this research are to know job satisfaction level of hygiene college staff Hangtuah Pekanbaru and also determinant of job satisfaction. Aims of this research is to know picture of job satisfaction and relevant factors with job satisfaction of hygiene vollege staff Hangtuah Pekanbaru in Riau Provice by using approach method Cross Sectional Study with 115 staff as sample. This research results are 50,4% unsatisfactory respondent, and there are 49,6% who satisfied. After conducted bivariate varible test which meaningful is marriage statue P value 0,003 and OR 3,446 while unmeaning age P value 0,264, gender P value 0,776, period of work P value 0,203, office statue P value 0,890 Thereby researcher suggest that decision maker in STIKES Hangtuah give enough developing opportunities to develop both thinking in work and also in carrier, give light work than heavy work, provide sufficiet income hence jobs satisfaction will be realized and otherwise if income less hence jobs satisfactory will be less too. Need an awareness for all respondent who not marriage that they need to contiuosly develob their skill and give solution each other between coworker if they met difficulties in their work cause seem that unmarried responderresponsders tended to unsatisfied.